Ensuring Food Safety in Indonesia’s Beef Industry: Strengthening the Halal Assurance System, Veterinary Control Number (NKV), and Hazard Analysis Critical Control Point HACCP Implementation - Fajri, Aulia Irhamni; Sihombing, Dewi Elfrida (Jurnal Teknologi Hasil Peternakan, 2025)
Indonesia’s beef industry encounters significant food safety challenges, primarily due to a high dependency on imported beef (43% of total supply) and the fragmented enforcement of domestic safety regulations (BPS, 2023). Three key quality assurance systems address these issues: the Halal Assurance System (HAS), the Veterinary Control Number (NKV), and the Hazard Analysis Critical Control Point (HACCP). HAS, mandated by Law No. 33 of 2014, ensures compliance with Islamic dietary laws. NKV, regulated by Government Regulation No. 95 of 2012, certifies hygiene and sanitation standards in meat processing. Based on SNI and Codex Alimentarius guidelines, HACCP enhances food safety by identifying and controlling hazards. This study employs a systematic literature review to analyze implementation, challenges, and potential improvements. Findings indicate that small and medium slaughterhouses (RPH) face financial and technical barriers in obtaining NKV and HACCP certification. Limited awareness and inconsistent enforcement further hinder compliance. Strengthening these systems requires government intervention, industry collaboration, and training programs. NKV is a prerequisite for HACCP, while HACCP reinforces HAS and NKV compliance. Integrating these frameworks is essential for enhancing food safety, increasing consumer trust, and boosting Indonesia's competitiveness in domestic and international markets.